Tree climbing tobot design, kinematics and motion planning - Lam, Tin Lun. (Springer tracts in advanced robotics,, 2012)
Climbing robot is a challenging research topic that has gained much attention from researchers. Most of the robots reported in the literature are designed to climb on manmade structures, but seldom robots are designed for climbing natural environment such as trees. Trees and manmade structures are very different in nature. It brings different aspects of technical challenges to the robot design. In this book, you can find a collection of the cutting edge technologies in the field of tree-climbing robot and the ways that animals climb. It provides a valuable reference for robot designers to select appropriate climbing methods in designing tree-climbing robots for specific purposes. Based on the study, a novel bio-inspired tree-climbing robot with several breakthrough performances has been developed and presents in this book. It is capable of performing various actions that is impossible in the state-of-the-art tree-climbing robots, such as moving between trunk and branches. This book also proposes several approaches in autonomous tree-climbing, including the sensing methodology, cognition of the environment, path planning and motion planning on both known and unknown environment.